Futures Panel: Telecommunications of the Future - Dean Gillette (Journal of Applied Communications, 1979)
In organizing the Futures Panel Mason Miller said that communication changes are going to make it more and more possible for us to communicate individually and to communicate more to each individual's needs and interests.